2017
DOI: 10.1155/2017/3718360
|View full text |Cite
|
Sign up to set email alerts
|

Group A Streptococci-Associated Necrotizing Fasciitis following Cat Bite in an Immunocompromised Patient

Abstract: Necrotizing soft tissue infections are characterized clinically by fulminant tissue destruction, systemic signs of toxicity, and high mortality. Accurate diagnosis and appropriate treatment must include early surgical intervention and antibiotic therapy. Mortality rate is very high and could be even higher in an immunocompromised host. We present a 57-year-old female with history of rheumatoid arthritis on oral corticosteroid and methotrexate therapy with painful swelling of the left hand following a cat bite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…However, in our literature review, we were unable to identify a case of an immunocompetent host who developed necrotizing fasciitis without a penetrating injury or inciting infection. Unique cases have been reported that include necrotizing fasciitis in an atraumatic immunocompromised host, another case from an intestinal perforation of a toothpick, and a another case from a simple cat bite [ 5 , 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in our literature review, we were unable to identify a case of an immunocompetent host who developed necrotizing fasciitis without a penetrating injury or inciting infection. Unique cases have been reported that include necrotizing fasciitis in an atraumatic immunocompromised host, another case from an intestinal perforation of a toothpick, and a another case from a simple cat bite [ 5 , 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%